Investigation of the Association between Psychological Well-being and Emotional Eating Habits in University Students enrolled in Health Departments - Aslan, Gülpınar; Gül Can, Fatma; Kant, Elif (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Psychological health plays a vital role in enabling students to successfully acclimate to university life. Individuals with diminished psychological well-being may be susceptible to developing behavioral health challenges, including feelings of inadequacy, low self-worth, self-harm, and eating disorders. This study aims to investigate the relationship between psychological well-being levels and emotional eating behaviors in university students enrolled in health departments. Methods: This descriptive study was conducted between February and April 2023 with 545 students who were enrolled in the Faculty of Health Sciences at a university. Data were collected through the Descriptive Characteristics Form, the Psychological Well-being Scale, and the Emotional Eating Scale. Normality distribution of the data was tested using skewness and kurtosis coefficients; analysis of the descriptive characteristics was performed using descriptive (percentages, arithmetic means, standard deviation, min-max) tests, t-test in independent groups, ANOVA test, Cronbach’s alpha reliability, and Pearson correlation analysis. Results: Participating individuals’ mean age was 20.88± 1.81, and 74.7% were women, 97.2% were single, 45.1% were nursing students, 49% had income equal to expenses, 57.1% were happy about their weight, 60.2% saw their weight normal, 88.3% did not have any health problems, 59.8% chose the department willingly, 79.8% loved their department, 65.7% had positive expectations about the future, and 71.7% had normal BMI (Body Mass Index). There was a notable difference in the mean scores on the Emotional Eating Scale in female students, in those who were enrolled in the nursing department, who were dissatisfied with their weight, who perceived themselves as overweight, and who were obese. On the other hand, the scores of Psychological Well-Being were higher in those who were content with their weight, who perceived their weight as normal, who willingly chose their department and enjoyed it, and who had positive expectations about the future. Conclusions: A significant, negative association was detected between the Control against Stimuli sub-scale of the Emotional Eating Scale and the Psychological Well-being Scale, while a significant, positive association was found between the self-control sub-scale and the Psychological Well-being Scale. In line with these results, it is recommended to implement psychological support programs for students to develop coping strategies for emotional eating (stress, anxiety, etc.), to identify students with body image dissatisfaction and guide them to relevant experts, and to provide multidisciplinary teamwork to eliminate obese students’ emotional eating behaviors.